Combining molecular fingerprints with multidimensional scaling analyses to identify the source of spilled oil from highly similar suspected oils. Issue 1 (15th April 2015) - Zhou, Peiyu; Chen, Changshu; Ye, Jianjun; Shen, Wenjie; Xiong, Xiaofei; Hu, Ping; Fang, Hongda; Huang, Chuguang; Sun, Yongge
Highlights: Oil fingerprints failed to differentiate the spilled oil from highly similar suspected oils. Specific biomarkers can be a quick scanning tool for determining the possible source. Multidimensional scaling analysis is introduced to pinpoint the source. Abstract: Oil fingerprints have been a powerful tool widely used for determining the source of spilled oil. In most cases, this tool works well. However, it is usually difficult to identify the source if the oil spill accident occurs during offshore petroleum exploration due to the highly similar physiochemical characteristics of suspected oils from the same drilling platform. In this report, a case study from the waters of the South China Sea is presented, and multidimensional scaling analysis (MDS) is introduced to demonstrate how oil fingerprints can be combined with mathematical methods to identify the source of spilled oil from highly similar suspected sources. The results suggest that the MDS calculation based on oil fingerprints and subsequently integrated with specific biomarkers in spilled oils is the most effective method with a great potential for determining the source in terms of highly similar suspected oils.